Assessment of Comprehensive Candidate Assessment Methods and Their Relationship to Academic Achievement and Student Retention - Alina Omirzak (Scientific Trends, 2025)
The article discusses current trends and problems of assessing students' academic achievements in higher education. Particular attention is paid to the holistic review method as a tool for increasing the inclusiveness and accuracy of applicant selection, taking into account academic, personal, motivational and social factors. Based on modern research and empirical data, the advantages and limitations of this approach, as well as its impact on academic success and student retention, are discussed. The main problems of implementing holistic review related to subjectivity, social inequality and high resource costs are identified.
Keywords: Higher education, assessment of academic achievements, adaptive testing, portfolio analysis, holistic review, academic success, student retention, inclusiveness, admissions policy.